Preparation, characterization and properties of biodegradable poly(butylene adipate‐co‐butylene terephthalate)/thermoplastic poly(propylene carbonate) polyurethane blend films. (5th October 2020) - Zhang, Ye; Jia, Shiling; Pan, Hongwei; Wang, Lijuan; Zhang, Huiliang; Yang, Huili; Dong, Lisong
Abstract : Poly(butylene adipate‐co‐terephthalate) (PBAT)/thermoplastic poly(propylene carbonate) polyurethane (PPCU)/ADR blend films were obtained by melt blending and blowing films technique. The rheological behavior, thermal properties, mechanical properties, barrier properties, water vapor permeability (WVP), wettability performances, optical properties, and biodegradability properties were investigated. Differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA) indicated that PBAT and PPCU had good miscibility. The addition of PPCU could reduce the crystallization process. All blend films exhibited good mechanical properties with high tensile strength of 42.1 to 66.6 MPa and elongation at break of 629% to 968% in the machine direction (MD) and tensile strength of 33.2 to 46.4 MPa and elongation at break of 1080% to 1665% in the transverse direction (TD). The thermal stability of PBAT/PPCU/ADR blend films was decreased when PPCU was added, however the processing and use of blend films were not affected. From barrier properties and WVP analysis, all PBAT/PPCU/ADR blend films showed good water vapor barrier properties and gas barrier performance. Surfaces of PBAT/PPCU/ADR blend films were hydrophobic with contact angle of 94.3° to 102.6°. All PBAT/PPCU/ADR blend films had high transparency. Biodegradability results showed that PPCU content could affect biodegradability of the films. This study indicates that PBAT/PPCU/ADR blend films as biodegradable packaging materials have great potential for application in fresh fruit and vegetable packaging, cosmetics and other industries in the future.